Apresente uma derivação à extrema esquerda (DEE) da sentença A := B * (C * (A + B)) sobre a gramática a seguir (Sebesta, 2000).
G = ({atr, exp, ter, fat, id}, {A, B, C, :=, +, *, (, )}, P, atr)
P = {< atr > -> < id > := < exp >
< exp > -> < exp > + < ter > | < ter >
< ter > -> < ter > * < fat > | < fat >
< fat > -> ( < exp > ) | < id >
< id > -> A | B | C }
< atr >
< id > := < exp >
A := < exp >
A := < ter >
A := < ter > * < fat >
A := < fat > * < fat >
A := < id > * < fat >
A := B * < fat >
A := B * ( < exp > )
A := B * ( < ter > )
A := B * ( < ter > * < fat > )
A := B * ( < fat > * < fat > )
A := B * ( < id > * < fat > )
A := B * ( C * < fat > )
A := B * ( C * ( < exp > ) )
A := B * ( C * ( < exp > + < ter > ) )
A := B * ( C * ( < ter > + < ter > ) )
A := B * ( C * ( < fat > + < ter > ) )
A := B * ( C * ( < id > + < ter > ) )
A := B * ( C * ( A + < ter > ) )
A := B * ( C * ( A + < fat > ) )
A := B * ( C * ( A + < id > ) )
A := B * ( C * ( A + B ) )